Corruption elimination in Malaysia: An analysis on public officials - Ahmad, N.S.Y.; Jaafar, J.L.S.; Sulaiman, A.N. (2010)
Corruption is a complex phenomenon that is almost never explained by a single cause. This paper aims to determine the relationship between economic strain, practices of religion and corruption practices among Malaysian civil service servants. Efforts undertaken to eliminate or curb corruption have failed to achieve total eradication. The rate can be reduced by most legal authorities but it is almost impossible to eliminate them. The study found that those involved and convicted appear to be mostly male officers. Economic strain was found to be associated negatively and significantly with religious strength. This implied that the economic strain influence the increase of corruption ‘crime’ among male officers as compared to women officers is of great important as it may be suggest the suitability of the Malaysian government or the federal government framework in controlling corruption for the Malaysian community. Unfortunately, the traditional norms and values is fast forgotten and disappearing due to the lack of effort to preserve them. Thus, this paper will try to discuss the issues related to the causes, consequences, scope of corruption and the role of the Malaysian government to fight against corruption among the public officials in Malaysia.